Positive electrode materials and secondary batteries
Patent Information
- Application Number
- CN201980042692.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-31
- Filing Date
- 2019-02-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2039-02-21
AI Technical Summary
The transition metal oxide with high Li content has high surface reactivity and is easy to decompose electrolytes, resulting in a decrease in the initial efficiency of the secondary battery.
An anhydride coating of dicarboxylic acid and/or dicarboxylic acid is formed on the surface of transition metal oxides with high Li content, inhibiting electrolyte decomposition and gas generation, and improving initial efficiency.
Through the coating, electrolyte decomposition and gas generation are suppressed, the initial efficiency of the secondary battery is improved, and high capacity is maintained during the charge and discharge cycle.
Smart Images

Figure CN112313817B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode material for a secondary battery and a secondary battery. Background Art
[0002] In order to increase the capacity of lithium ion batteries, attempts have been made to use high-Li-content transition metal oxides in which the content ratio of lithium to oxygen is large.
[0003] For example, Patent Document 1 discloses the use of Li 2 NiO 2 as a positive electrode active material having a large theoretical capacity.
[0004] Patent Document 2 discloses the use of Li2NiO2 and lithium-containing transition metal oxide LiNi 0.8 Co 0.15 Al 0.05 An example of a lithium secondary battery composed of a positive electrode active material mixed with O2 in a ratio of 5:95.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 9-241026
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-536541 Summary of the invention
[0009] Problem that the invention aims to solve
[0010] On the other hand, the surface reactivity of a transition metal oxide having a high Li content is high, and a side reaction accompanied by electrolyte decomposition is likely to proceed, so the initial efficiency of the secondary battery is likely to decrease.
[0011] Solutions for solving problems
[0012] One aspect of the present invention relates to a secondary battery positive electrode material comprising: a high-Li-content transition metal oxide having an atomic ratio of lithium to oxygen: Li / O of 0.8 or more; and a dicarboxylic acid and / or an anhydride of the dicarboxylic acid.
[0013] Another aspect of the present invention relates to a secondary battery including: a positive electrode including the positive electrode material according to the one aspect, a negative electrode, and an electrolyte.
[0014] Effects of the Invention
[0015] According to the positive electrode material of the present invention, the side reaction of the secondary battery is suppressed and the initial efficiency is improved.
[0016] Although the novel features of the present invention are described in the appended claims, the present invention relates to both structural and content aspects, which will be better understood through the following detailed description taken in conjunction with other objects and features of the present invention and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a partially cutaway perspective view of a secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0018] The positive electrode material according to the embodiment of the present invention includes: a high-Li-content transition metal oxide having an atomic ratio of lithium to oxygen: Li / O of 0.8 or more; and a dicarboxylic acid and / or an anhydride of a dicarboxylic acid (hereinafter also referred to as "dicarboxylic acid / anhydride").
[0019] In the present invention, the positive electrode material refers to a concept including raw materials for forming a positive electrode (positive electrode active material powder, etc.), intermediates (positive electrode mixture containing positive electrode active material, slurry formed by dispersing the positive electrode mixture in a liquid dispersion medium, etc.), the positive electrode material layer possessed by the completed positive electrode, the positive electrode active material and positive electrode mixture taken out from the completed positive electrode, etc.
[0020] Dicarboxylic acid / acid anhydride can form a good coating on the surface of a transition metal oxide with a high Li content. That is, at least a portion of the surface of the positive electrode material can be covered with a coating derived from a dicarboxylic acid / acid anhydride. Through the coating, the electrolyte decomposition and gas generation starting from the surface of the transition metal oxide with a high Li content are suppressed, and the initial efficiency is improved. The coating derived from dicarboxylic acid / acid anhydride is usually formed by introducing lithium ions, so it contains lithium, oxygen and carbon.
[0021] As the transition metal element contained in the transition metal oxide with high Li content, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Zr, W, etc. can be mentioned. The lithium-containing transition metal oxide can contain one transition metal element, or it can contain more than two. The transition metal oxide with high Li content can, for example, include at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe. Among them, it is preferred to contain at least one of Ni and Fe. The transition metal oxide with high Li content can contain one or more typical metal elements as needed. As typical metal elements, Mg, Al, Ca, Zn, Ga, Ge, Sn, Sb, Pb, Bi, etc. can be mentioned.
[0022] When the transition metal oxide with a high Li content contains Ni and / or Fe, the ratio of the total of Ni and / or Fe in the total of the transition metal element and the typical metal element may be 50 atomic % or more, or 80 atomic % or more.
[0023] Examples of transition metal oxides with high lithium content include Li x1 M 1 A 1 2 represents lithium and metal element M satisfying 1.5≤x1≤2.3 1 A composite oxide (hereinafter appropriately referred to as "the first composite oxide"). 1 Contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe. 1 At least oxygen. 1 The ratio of the first composite oxide to the first composite oxide is 85 atomic % or more.
[0024] The first composite oxide may contain Ni, for example. In the first composite oxide, Ni is present in the M 1 The ratio of may be 50 atomic % or more, or 80 atomic % or more.
[0025] As a typical example of the first composite oxide, more specifically, Li2NiO2 can be cited. Li2NiO2 has a crystal structure belonging to the space group Immm. In Li2NiO2, four oxygen atoms are planarly coordinated around Ni to form a planar 4-coordinated NiO4 cluster. Adjacent NiO4 clusters are connected to each other on the same plane by sharing two O atoms to form a planar one-dimensional straight chain composed of NiO2. The straight chains of the above-mentioned NiO2 are stacked in a manner that the planes of each straight chain are parallel to each other to form a layered structure. Li exists between the one-dimensional straight chains of NiO2 in the above-mentioned layered structure. More specifically, Li is coordinated with two oxygen atoms at the side ends of the one-dimensional straight chain of NiO2, and is coordinated with one oxygen atom each of the one-dimensional straight chains of NiO2 located on the upper and lower layers thereof, thereby being tetrahedrally coordinated with the O atoms.
[0026] In Li2NiO2, Ni exists as a divalent cation. When lithium ions are released from Li2NiO2 by charging, Ni can become a trivalent or tetravalent cation. However, as the valence state of Ni changes, it is difficult to maintain the planar structure of the above-mentioned NiO4. Therefore, it is easy to change into a crystal structure that cannot absorb Li ions, and the irreversible capacity is large.
[0027] In order to suppress the change of the crystal structure during Li release, a part of the element M in the first composite oxide may be 1 Replace with other metal elements, and / or replace part of oxygen atoms with other elements. For example, Li x1 M 1A 1-x2 M 1B x2 O 2-y A2 y (0≤x2≤0.5, 0≤y≤0.3, at least one of x2 and y is not 0). 1A M is a main metal element constituting the lithium composite oxide, and is at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe. 1B is a permutation M 1 The metal element comprises at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta and W. The oxygen-replacing element A 2 The present invention contains at least one selected from the group consisting of F, Cl, Br, S, and P.
[0028] Another example of a transition metal oxide with a high lithium content is Li x3 M 2 O z Lithium and metal element M that satisfy 4≤x3≤7 and 3.5≤z≤5 2 A composite oxide (hereinafter appropriately referred to as "the second composite oxide"). 2 The second composite oxide contains at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe. The second composite oxide belongs to the space group Pbca.
[0029] The second composite oxide may contain Fe, for example. 2 The ratio of may be 50 atomic % or more, or 80 atomic % or more.
[0030] As a typical example of the second composite oxide, more specifically, Li5FeO4 can be cited. Li5FeO4 has a crystal structure belonging to the space group Pbca. Li5FeO4 has a structure in which Li or Fe is arranged at the cation site of Li2O having an inverse fluorite structure. On the other hand, a part of the cation site forms a hole, through which a large amount of lithium ions can be absorbed.
[0031] The dicarboxylic acid / acid anhydride is not added to the electrolyte but is added to the positive electrode material before assembling the secondary battery. By adding the dicarboxylic acid / acid anhydride to the positive electrode material in advance, a good coating is formed on the surface of the transition metal oxide with a high lithium content.
[0032] A portion of the dicarboxylic acid / acid anhydride contained in the positive electrode material can be dissolved in the electrolyte in the battery. However, when the positive electrode material taken out of the battery is analyzed, the dicarboxylic acid / acid anhydride previously added to the positive electrode material can be detected.
[0033] It should be noted that when only dicarboxylic acid / acid anhydride is added to the electrolyte, it is difficult to form a film on the surface of a transition metal oxide having a high Li content.
[0034] In the manufacture of secondary batteries, the positive electrode is usually prepared by applying a positive electrode slurry containing a positive electrode mixture and a liquid dispersion medium to the surface of a positive electrode collector and drying it. The positive electrode mixture contains particles of a positive electrode active material and a binder (binding agent) as essential components. Since the alkalinity of transition metal oxides with a high lithium content is strong, the binder component (e.g., polyvinylidene fluoride (PVdF)) in the positive electrode slurry reacts and may produce hydrogen fluoride (HF).
[0035] By including dicarboxylic acid / acid anhydride in the positive electrode slurry in advance, the strong alkalinity of the positive electrode slurry is neutralized, and the generation of hydrogen fluoride can be suppressed. Therefore, the manufacturing process is stabilized, and a high-quality positive electrode is easily obtained.
[0036] As described above, since the dicarboxylic acid / acid anhydride is used to form a coating on the surface of the transition metal oxide with a high lithium content as the positive electrode active material, it is preferably retained in the positive electrode material. Therefore, the dicarboxylic acid / acid anhydride is preferably solid at room temperature and has a low solubility in the electrolyte.
[0037] The electrolyte uses a highly polar solvent. From the viewpoint of making the solubility in the electrolyte lower, the dicarboxylic acid / acid anhydride preferably has no more polar groups such as halogen groups, hydroxyl groups, and amino groups except the carboxyl group. In addition, the more carbons in the hydrocarbon chain bonded to the carbonyl carbon, the weaker the polarity of the dicarboxylic acid, and the easier it is for the solubility in the electrolyte to decrease. On the other hand, from the viewpoint of forming a film as dense as possible on the positive electrode active material, it is preferred that the hydrocarbon chain bonded to the carbonyl carbon has a small number of carbons.
[0038] Among dicarboxylic acids / acid anhydrides, acid anhydrides easily form a dense film on the surface of transition metal oxides with a high Li content. In addition, by using an acid anhydride, when a non-aqueous electrolyte is used, it is possible to suppress the mixing of water into the non-aqueous electrolyte due to the dehydration condensation of the dicarboxylic acid.
[0039] From the viewpoint of lowering the solubility in the electrolyte and forming a dense film on the surface of the transition metal oxide with a high Li content, the carbon number (including the carbonyl carbon) of the dicarboxylic acid / anhydride is preferably 3 to 6. Examples of the compound satisfying the above conditions include malonic acid and maleic anhydride.
[0040] The transition metal oxide with high lithium content can be mixed with other positive electrode active materials that can release lithium ions. As other positive electrode active materials, Li x4 M 3 O2 represents lithium and metal element M satisfying 0.8≤x4≤1.2 3 A composite oxide (hereinafter appropriately referred to as "the third composite oxide").3 It contains at least one selected from the group consisting of Ni, Co, Mn, Cu, Fe, and Cr. The above-mentioned third composite oxide belongs to the space group R-3m. Since the third composite oxide has a small expansion and contraction of the crystal lattice during charge and discharge, it is not easily deteriorated even in the above-mentioned electrolyte, and excellent cycle characteristics can be easily obtained.
[0041] The third composite oxide has a small irreversible capacity and is excellent in terms of initial efficiency. By using a transition metal oxide with a high Li content in combination with the third composite oxide, a positive electrode material with a high initial capacity and capable of maintaining a high capacity even after repeated charge and discharge cycles can be obtained.
[0042] When the positive electrode material contains the third composite oxide, the proportion of the transition metal oxide with a high Li content in the total of the transition metal oxide with a high Li content and the third composite oxide can be 0.3 to 20% by mass. By including the transition metal oxide with a high Li content within this range, the initial capacity of the entire positive electrode material is increased, and the capacity reduction caused by repeated charge and discharge cycles is also suppressed.
[0043] When a secondary battery is prepared using the positive electrode material of the embodiment of the present invention, a material used in a conventional lithium ion secondary battery can be used as the negative electrode material.
[0044] In particular, the negative electrode active material preferably contains an alloy-based material containing at least one element selected from the group consisting of Si, Sn, Ga, and In. As the alloy-based material containing Si, for example, elemental silicon, silicon alloy, and silicon compound can be cited. As the alloy-based material containing Sn, for example, elemental tin, tin alloy, and tin compound can be cited. As the alloy-based material containing Ga or In, Ga alloy and In alloy can be cited. As the silicon compound and tin compound, oxides and / or nitrides can be cited respectively. Among the alloy-based materials containing Si, SiO x (0.5 ≤ x < 2.0), lithium silicate composite particles are preferably used. Here, SiO x is a composite particle in which fine silicon is dispersed in the SiO2 phase. The lithium silicate composite particle is a composite particle in which fine silicon is dispersed in the lithium silicate phase (for example, Li 2x SiO 2+x (0 < x < 2)).
[0045] Although these alloy materials have high capacity, the initial efficiency is small, and the number of lithium ions that are irreversibly captured in the initial charge and do not contribute to the capacity in the subsequent charge and discharge is large. However, in the case where the positive electrode material comprises a transition metal oxide with a high Li content, the irreversible capacity of the negative electrode can be offset by the irreversible capacity of the positive electrode. That is, the lithium ions irreversibly consumed in the negative electrode can be supplied by the lithium ions irreversibly released by the transition metal oxide with a high Li content. Thus, in the charge and discharge cycle after the initial charge and discharge, a secondary battery with suppressed capacity reduction can be obtained.
[0046] A portion of the positive electrode material may have a LiM 4 An amorphous structure with O2 as the main component; a transition metal oxide with any one selected from the group consisting of LiFeO2, CoO and MnO as the main component; and / or a transition metal oxide with a complex of at least two selected from the group consisting of LiFeO2, CoO and MnO as the main component (hereinafter referred to as "amorphous structure"). 4 Contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe. Amorphous structures are structures that are difficult to occlude and release lithium ions due to charge and discharge. During initial charging, lithium ions are deintercalated from transition metal oxides with high Li content, and thus a part of the transition metal oxides with high Li content can be converted into amorphous structures. At this time, sometimes there are side reactions such as oxygen deintercalation, which can be considered as one of the reasons for the initial reduction in efficiency. On the other hand, in the case of containing dicarboxylic acid / acid anhydride in the positive electrode, side reactions such as oxygen deintercalation promote the formation of a high-quality film with dicarboxylic acid / acid anhydride, inhibiting the decomposition of the electrolyte and gas generation.
[0047] It should be noted that LiM 4 The amorphous structure in which O2 is the main component refers to a state in which the half-peak width w of the diffraction line corresponding to the (101) plane of a transition metal oxide with a high Li content obtained by, for example, X-ray diffraction measurement is w>0.5°. From the viewpoint of improving the inhibitory effect of electrolyte decomposition brought about by the amorphous structure, w>1.5° is preferred.
[0048] In addition, in the positive electrode active material formed by mixing the third composite oxide with the transition metal oxide with a high Li content, when the half-peak width of the diffraction line corresponding to the (101) plane of the transition metal oxide with a high Li content obtained by X-ray diffraction measurement is 7 times or more of the half-peak width of the strongest diffraction line of the third composite oxide, it can be said that a part of the positive electrode material has a LiM 4 The amorphous structure is mainly composed of O2. From the viewpoint of improving the inhibitory effect of electrolyte decomposition caused by the amorphous structure, the half-peak width of the transition metal oxide with a high Li content is preferably 10 times or more of the half-peak width of the strongest diffraction line of the third composite oxide.
[0049] In the present invention, the X-ray diffraction measurement method and the analysis conditions of the obtained data are as follows, for example.
[0050] Measurement device: MiniFlex, a tabletop X-ray diffraction device manufactured by Rigaku Corporation
[0051] Analysis software: Rigaku Corporation, comprehensive powder X-ray analysis software PDXL
[0052] Measurement conditions: 10°~80°
[0053] For cathode: Cu-Kα
[0054] Tube voltage: 40kV
[0055] Tube current: 10mA
[0056] Counting time: 0.5 seconds
[0057] Divergence slit: 1.25°
[0058] Scattering slit: 8.0mm
[0059] Light receiving slit: 13.0mm
[0060] The diffraction line of the (101) plane of the transition metal oxide having a high Li content (2θ=25 to 26°) and the strongest diffraction line of the third composite oxide are used.
[0061] Figure 1 It is a perspective view schematically showing a secondary battery according to one embodiment of the present invention. Figure 1 In FIG. 1 , a part of the main part of the secondary battery 1 is cut away to show the structure of the main part.
[0062] The secondary battery 1 includes a positive electrode, a negative electrode including a negative electrode material, and an electrolyte. The positive electrode includes a positive electrode material including the above-mentioned transition metal oxide with a high lithium content.
[0063] Figure 1 In the example of , the positive electrode and the negative electrode are wound with a separator sandwiched therebetween to form a flat wound electrode group 10. The electrode group 10 is housed in a square battery case 11 together with an electrolyte (not shown), thereby realizing a square wound battery. However, in the present invention, there is no particular limitation on the type, shape, etc. of the secondary battery.
[0064] One end of a positive lead 14 is connected to the positive current collector of the positive electrode included in the electrode group 10. The other end of the positive lead 14 is connected to a sealing plate 12 that functions as a positive terminal. One end of a negative lead 15 is connected to the negative current collector, and the other end of the negative lead 15 is connected to a negative terminal 13 disposed approximately in the center of the sealing plate 12. A gasket 16 is disposed between the sealing plate 12 and the negative terminal 13 to insulate the two. A frame 18 formed of an insulating material is disposed between the sealing plate 12 and the electrode group 10 to insulate the negative lead 15 from the sealing plate 12. The sealing plate 12 is joined to the open end of the square battery case 11 to seal the square battery case 11. An injection hole 17a is formed on the sealing plate 12, and the electrolyte is injected into the square battery case 11 from the injection hole 17a. Then, the injection hole 17a is sealed by a sealing plug 17.
[0065] (positive electrode)
[0066] The positive electrode comprises a positive electrode current collector and a positive electrode material layer (positive electrode material) disposed on the surface of the positive electrode current collector. The positive electrode current collector may be a sheet-shaped current collector. The positive electrode material layer contains a positive electrode active material. The positive electrode material layer may be formed on one surface of the sheet-shaped positive electrode current collector or on both surfaces.
[0067] (Positive electrode collector)
[0068] Examples of the positive electrode current collector include metal foils and metal sheets. Materials for the positive electrode current collector include stainless steel, aluminum, aluminum alloys, titanium, and the like. The thickness of the positive electrode current collector can be selected from a range of, for example, 3 to 50 μm.
[0069] (Positive electrode material layer)
[0070] The case where the positive electrode material layer is formed by a mixture (positive electrode mixture) containing positive electrode active material particles is described. The positive electrode material layer may contain a positive electrode active material, a dicarboxylic acid / acid anhydride and a binder as essential components, and a conductive agent as an optional component. The amount of binder contained in the positive electrode material layer is preferably 0.1 to 20 parts by mass, more preferably 1 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material. The thickness of the positive electrode material layer is, for example, 10 to 100 μm.
[0071] The positive electrode active material comprises the above-mentioned transition metal oxide with high Li content. Other known positive electrode materials having the function of occluding and releasing lithium ions can also be used in combination with the transition metal oxide with high Li content. As an example of such a positive electrode material, although not limited, lithium-containing transition metal oxides are preferred. As transition metal elements, Sc, Y, Mn, Fe, Co, Ni, Cu, Cr, Zr, W, etc. can be cited. Among these, Ni, Co, Mn, Fe, Cu, Cr are preferred, and Mn, Co, Ni are more preferred. For lithium-containing transition metal oxides, lithium nickel composite oxides containing Li, Ni and other metals are preferred in terms of obtaining high capacity.
[0072] The lithium-containing transition metal oxide may contain one or more typical metal elements as required. Typical metal elements include Mg, Al, Ca, Zn, Ga, Ge, Sn, Sb, Pb, Bi, etc. Typical metal elements may also be Al, etc.
[0073] Examples of lithium-containing transition metal oxides used in combination with the transition metal oxide with a high lithium content include the third composite oxide Li belonging to the space group R-3m. a M 3 O2(M 3 Contains at least one selected from the group consisting of Ni, Co, Mn, Cu, Fe and Cr, 0.8≤a≤1.2).
[0074] The third composite oxide may also contain Ni, Co, and Mn and / or Al, for example. In such a positive electrode active material, the ratio of Ni to the sum of Ni, Co, Mn and Al may be 50 atomic % or more. For example, in the case where the positive electrode active material contains Ni, Co and Al, the ratio of Ni may be 50 atomic % or more, or 80 atomic % or more. In the case where the positive electrode active material contains Ni, Co and Mn, the ratio of Ni may also be 50 atomic % or more.
[0075] Specific examples of lithium-containing transition metal oxides (third composite oxides) include lithium-nickel-cobalt-manganese composite oxides (LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.4 Co 0.2 Mn 0.4 O2, etc.), lithium-nickel-cobalt composite oxide (LiNi 0.8 Co 0.2 O2, etc.), lithium-nickel-cobalt-aluminum composite oxide (LiNi 0.8Co 0.15 Al 0.05 O2、LiNi 0.8 Co 0.18 Al 0.02 O2、LiNi 0.88 Co 0.09 Al 0.03 O2) etc.
[0076] When the positive electrode active material contains the high-Li transition metal oxide and the third composite oxide, the ratio of the high-Li transition metal oxide to the total of the high-Li transition metal oxide and the third composite oxide is preferably 0.3 to 20 mass %.
[0077] From the viewpoint of improving the filling property of the positive electrode active material in the positive electrode material layer, it is desired that the average particle size (D50) of the positive electrode active material particles is sufficiently small relative to the thickness of the positive electrode material layer. The average particle size (D50) of the positive electrode active material particles is, for example, preferably 5 to 30 μm, more preferably 10 to 25 μm. It should be noted that the average particle size (D50) refers to the median particle size when the cumulative volume in the volume-based particle size distribution is 50%. The average particle size is measured, for example, using a laser diffraction / scattering particle size distribution measuring device.
[0078] The positive electrode material layer includes dicarboxylic acid / acid anhydride. The dicarboxylic acid / acid anhydride can cover at least a portion of the surface of the positive electrode active material particles. Thus, a coating containing lithium, oxygen and carbon can be formed on at least a portion of the surface of the positive electrode active material particles. In addition, the coating can cover at least a portion of the surface of the binder and at least a portion of the surface of the conductive agent.
[0079] The proportion of dicarboxylic acid / acid anhydride in the positive electrode material layer (positive electrode material) as a whole can be 0.1 to 10% by mass. By making the positive electrode material contain more than 0.1% by mass of dicarboxylic acid / acid anhydride, a coating can be formed on the surface of the positive electrode active material particles, which can inhibit the decomposition of the electrolyte. On the other hand, as the content ratio of dicarboxylic acid / acid anhydride increases, the content ratio of the positive electrode active material decreases, so the capacity decreases. In addition, the film thickness of the coating becomes thicker, and the release of lithium ions is hindered, which leads to higher resistance and easier reduction of capacity.
[0080] When the positive electrode material contains dicarboxylic acid / acid anhydride in a range of 10 mass % or less, a high capacity can be maintained.
[0081] Examples of binders include fluororesins such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), and tetrafluoroethylene-hexafluoropropylene copolymer (HFP); acrylic resins such as polymethyl acrylate and ethylene-methyl methacrylate copolymer; rubber-like materials such as styrene-butadiene rubber (SBR) and acrylic rubber; and water-soluble polymers such as carboxymethyl cellulose (CMC) and polyvinyl pyrrolidone.
[0082] As the conductive agent, carbon black such as acetylene black and Ketjen black is preferred.
[0083] The positive electrode material layer can be formed by mixing positive electrode active material particles, dicarboxylic acid and / or dicarboxylic acid anhydride, a binder, etc. with a dispersion medium to prepare a positive electrode slurry, applying the positive electrode slurry to the surface of the positive electrode collector, and rolling after drying. As the dispersion medium, water; alcohols such as ethanol; ethers such as tetrahydrofuran; N-methyl-2-pyrrolidone (NMP) and the like are used.
[0084] In the case where the positive electrode active material contains a transition metal oxide with a high lithium content, the alkalinity of the positive electrode slurry is easily enhanced. Under strong alkali, the PVdF contained as a binder reacts and easily produces hydrogen fluoride (HF). The generated hydrogen fluoride easily deteriorates the positive electrode. However, by making the positive electrode slurry contain dicarboxylic acid, the alkalinity of the positive electrode slurry can be weakened and the reaction of PVdF can be suppressed.
[0085] (negative electrode)
[0086] The negative electrode has a negative electrode collector. The negative electrode collector can use a sheet-shaped collector. The negative electrode can also have a negative electrode material layer (negative electrode material) arranged on the surface of the negative electrode collector. The negative electrode material layer contains a negative electrode active material that can absorb and release lithium. The negative electrode material layer can be formed on one surface of the negative electrode collector, or it can be formed on both surfaces.
[0087] Since the secondary battery of the embodiment of the present invention can obtain a high positive electrode capacity, the negative electrode active material capable of absorbing lithium ions in the negative electrode is easily insufficient relative to the lithium ions released in the positive electrode. More specifically, for example, the secondary battery can also be a battery in which metallic lithium is precipitated on the negative electrode (negative electrode collector and / or negative electrode active material) under a charging state of 4.3V.
[0088] (Negative electrode current collector)
[0089] Examples of the negative electrode current collector include metal foil, metal sheet, mesh, punched sheet, expanded metal, etc. The negative electrode current collector may be made of stainless steel, nickel, copper, copper alloy, etc. The thickness of the negative electrode current collector may be selected from the range of 3 to 50 μm, for example.
[0090] (Negative electrode material layer)
[0091] The negative electrode material layer can be formed using a negative electrode slurry containing a negative electrode active material, a binder (binding agent) and a dispersion medium according to the method for manufacturing the positive electrode material layer. The negative electrode material layer may also contain optional components such as a conductive agent as needed. The amount of binder contained in the negative electrode material layer is preferably 0.1 to 20 parts by mass, more preferably 1 to 5 parts by mass relative to 100 parts by mass of the negative electrode material layer. The thickness of the negative electrode material layer is, for example, 10 to 100 μm.
[0092] The negative electrode active material may be a non-carbon material, a carbon material, or a combination thereof. The carbon material used as the negative electrode active material is not particularly limited, but is preferably at least one selected from the group consisting of graphite and hard carbon. Among them, graphite is more preferred because it has a high capacity and a small irreversible capacity.
[0093] Graphite is a general term for carbon materials with a graphite structure, including natural graphite, artificial graphite, expanded graphite, graphitized mesophase carbon particles, etc. Examples of natural graphite include flaky graphite and earthy graphite. Generally, the interplanar spacing d of the 002 plane of the graphite structure calculated from the X-ray diffraction spectrum is 002 Carbon materials with a 0.02-0.10 angstrom spacing d are classified as graphite. On the other hand, hard carbon is a carbon material in which minute graphite crystals are arranged in random directions and graphitization is almost non-existent. 002 Greater than 3.44 angstroms.
[0094] As the non-carbon material used as the negative electrode active material, an alloy material is preferred. The alloy material preferably includes any one selected from silicon, tin, Ga, and In, and silicon alone and silicon compounds are preferred. Silicon compounds include silicon oxides and silicon alloys.
[0095] As the negative electrode active material, metallic lithium or a lithium alloy may be used.
[0096] (Separator)
[0097] As the separator, a microporous film, nonwoven fabric, woven fabric, etc. made of resin can be used. As the resin, polyolefins such as polyethylene (PE) and polypropylene (PP), polyamide, polyamide-imide, etc. can be used.
[0098] (Electrolytes)
[0099] The electrolyte includes a solvent and a solute dissolved in the solvent. Various lithium salts can be used as the solute. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may also contain a known additive.
[0100] Examples of the solvent include non-aqueous solvents such as cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, and water.
[0101] As cyclic carbonate, ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), butylene carbonate, vinylene carbonate, vinyl ethylene carbonate and their derivatives etc. can be used.They can be used alone, and more than 2 kinds can also be used in combination.From the viewpoint of the ionic conductivity of electrolyte, preferably use at least one selected from the group consisting of ethylene carbonate, fluoroethylene carbonate, propylene carbonate.
[0102] Examples of the chain carbonate include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC).
[0103] Examples of the cyclic carboxylic acid ester include γ-butyrolactone (GBL) and γ-valerolactone (GVL).
[0104] As the chain carboxylic acid ester, methyl acetate (MA), ethyl acetate (EA), propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and the like can be used.
[0105] These solvents may be used alone or in combination of two or more.
[0106] Examples of the lithium salt include LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(SO2F)2, and LiN(SO2CF3)2. The lithium salt may be used alone or in combination of two or more.
[0107] [Example]
[0108] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0109] 《Example 1》
[0110] A secondary battery using Li5FeO4 as a positive electrode active material was produced according to the following procedure.
[0111] (1) Preparation of positive electrode
[0112] As the transition metal oxide having a high Li content, Li 5 FeO 4 was used as the second composite oxide, LiCoO 2 was used as the third composite oxide, and malonic acid (MAL) was used as the dicarboxylic acid.
[0113] Li5FeO4, LiCoO2, MAL, acetylene black (AB) as a conductive material and polyvinylidene fluoride (PVdF) as a binder were mixed in a mass ratio of Li5FeO4: LiCoO2: MAL: AB: PVdF = 4: 93.1: 1: 1: 0.9, and N-methyl-2-pyrrolidone (NMP) was added in an appropriate amount and stirred to prepare a positive electrode slurry. Then, the obtained positive electrode slurry was applied to one side of an aluminum foil (positive electrode collector) and dried, and the coating of the positive electrode mixture layer was rolled using a roller.
[0114] The obtained laminate of the positive electrode current collector and the positive electrode mixture layer is cut into an electrode size to produce a positive electrode including a positive electrode material layer on one side of the positive electrode current collector.
[0115] (2) Preparation of negative electrode
[0116] Artificial graphite as a negative electrode active material, sodium salt of carboxymethyl cellulose as a thickener, and styrene-butadiene copolymer as a binder are mixed in a mass ratio of 100:1:1 to prepare a negative electrode slurry. Next, the obtained negative electrode slurry is applied to a single side of a negative electrode collector composed of copper foil. After the coating film is dried, the coating film of the negative electrode mixture layer is rolled using a roller. The obtained laminate of the negative electrode collector and the negative electrode mixture layer is cut into an electrode size to produce a negative electrode having a negative electrode material layer on a single side of the negative electrode collector.
[0117] (3) Preparation of electrolyte
[0118] A non-aqueous solvent was obtained by adding 1 part by mass of vinylene carbonate to 100 parts by mass of a mixed solution containing EC and EMC at a mass ratio of 1:3. LiPF6 was dissolved in the non-aqueous solvent at a concentration of 1.0 mol / L to prepare an electrolyte.
[0119] (4) Battery production
[0120] Leads were attached to the positive electrode and negative electrode obtained above, respectively. An electrode body was prepared in which the positive electrode and the negative electrode were facing each other with a separator of 0.015 mm thick made of PP and PE sandwiched therebetween. The electrode body was sealed in an outer casing made of aluminum laminate film together with an electrolyte, thereby preparing a secondary battery A1.
[0121] (5) Evaluation
[0122] Charge at a constant current of 0.05C until the closed-circuit voltage of the battery reaches 4.35V, then charge at a constant voltage of 4.35V until the current value falls below 0.02C, and calculate the initial charge capacity C1 of the battery.
[0123] Thereafter, the battery was discharged at a constant current of 0.05 C until the closed circuit voltage of the battery reached 2.5 V, and the discharge capacity C2 was obtained. X=C2 / C1 was used as the initial efficiency for evaluation. Note that the charge and discharge were performed at 25°C.
[0124] 《Example 2》
[0125] In the production of the positive electrode, a positive electrode slurry was prepared by mixing Li5FeO4:LiCoO2:MAL:AB:PVdF at a mass ratio of 4:89.1:5:1:0.9.
[0126] A secondary battery A2 was produced in the same manner as in Example 1 except for the above.
[0127] Comparative Example 1
[0128] In the production of the positive electrode, a positive electrode slurry to which malonic acid was not added was used.
[0129] A secondary battery B1 was produced in the same manner as in Example 1 except that a positive electrode slurry was prepared in which Li5FeO4:LiCoO2:AB:PVdF was mixed in a mass ratio of 4:9 to 4.1:1:0.9.
[0130] The evaluation results of the initial charge capacity C1 and the initial efficiency X of Examples 1 and 2 and Comparative Example 1 are shown in Table 1. In Table 1, the initial efficiency X is expressed as a relative value when the initial efficiency of the battery B1 is set to 100.
[0131] 《Reference Example 1》
[0132] In the preparation of the positive electrode, a positive electrode slurry is used to which no transition metal oxide with a high lithium content and no malonic acid are added.
[0133] LiCoO2 as the third composite oxide, acetylene black (AB) as the conductive material, and polyvinylidene fluoride (PVdF) as the binder were mixed at a mass ratio of LiCoO2:AB:PVdF=98.1:1:0.9, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added and stirred to prepare a positive electrode slurry. Secondary battery C1 was prepared in the same manner as in Example 1 except for the above.
[0134] 《Reference Example 2》
[0135] In Reference Example 1, a positive electrode slurry to which malonic acid was added was used.
[0136] That is, LiCoO2, MAL, acetylene black (AB) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed at a mass ratio of LiCoO2:MAL:AB:PVdF=97.1:1:1:0.9, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added and stirred to prepare a positive electrode slurry. Other than this, a secondary battery C2 was prepared in the same manner as in Example 1.
[0137] Table 1 shows the results of evaluating the initial charge capacity C1 of Reference Examples 1 and 2 in the same manner.
[0138] 《Example 3》
[0139] A secondary battery using Li2NiO2 as a positive electrode active material was produced according to the following steps.
[0140] (1) Preparation of positive electrode
[0141] As the transition metal oxide with high lithium content, the first composite oxide Li2NiO2 is used, and LiNi 0.82 Co 0.15 Al 0.03 O2 was used as the third composite oxide, and maleic anhydride (MALE) was used as the dicarboxylic acid.
[0142] Li2NiO2、LiNi 0.82 Co 0.15 Al 0.03 O2, MALE, acetylene black (AB) as a conductive material and polyvinylidene fluoride (PVdF) as a binder with Li2NiO2: LiNi 0.82 Co 0.15 Al 0.03 O2:MALE:AB:PVdF=20:80:1:1:0.9 mass ratio is mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) is further added and stirred to prepare a positive electrode slurry. Then, the obtained positive electrode slurry is applied to one side of an aluminum foil (positive electrode collector) and dried, and the coating of the positive electrode mixture layer is rolled using a roller. The obtained stack of the positive electrode collector and the positive electrode mixture layer is cut into an electrode size to produce a positive electrode having a positive electrode material layer on one side of the positive electrode collector.
[0143] A secondary battery A3 was produced in the same manner as the battery A1 of Example 1 except for the above.
[0144] (2) Evaluation
[0145] Charge at a constant current of 0.05C until the closed-circuit voltage of the battery reaches 4.2V, then charge at a constant voltage of 4.2V until the current value falls below 0.02C, and calculate the initial charge capacity C1 of the battery.
[0146] Thereafter, the battery was discharged at a constant current of 0.05 C until the closed circuit voltage of the battery reached 2.5 V, and the discharge capacity C2 was obtained. X=C2 / C1 was used as the initial efficiency for evaluation. Note that the charge and discharge were performed at 25°C.
[0147] Comparative Example 2
[0148] In the production of the positive electrode, a secondary battery B2 was produced in the same manner as in Example 3 except that a positive electrode slurry to which maleic anhydride was not added was used.
[0149] The evaluation results of the initial charge capacity C1 and the initial efficiency X of Example 3 and Comparative Example 2 are shown in Table 2. In Table 2, the initial efficiency X is expressed as a relative value when the initial efficiency of the battery B2 is set to 100.
[0150] [Table 1]
[0151]
[0152] [Table 2]
[0153]
[0154] As shown in Table 1, in batteries A1 and A2 in which a transition metal oxide with a high Li content and a dicarboxylic acid are added to the positive electrode slurry, the initial charge capacity C1 is high and the initial efficiency X is also improved compared to battery B1 in which only a transition metal oxide with a high Li content is added to the positive electrode slurry without adding a dicarboxylic acid.
[0155] As shown in Table 2, in the battery A3 in which a transition metal oxide with a high Li content and an anhydride of a dicarboxylic acid were added to the positive electrode slurry, the initial charge capacity C1 was higher than that of the battery B2 in which only a transition metal oxide with a high Li content was added to the positive electrode slurry without adding an anhydride of a dicarboxylic acid, and an improvement in the initial efficiency X was observed.
[0156] The initial charge capacity of battery A2 is lower than that of battery A1. The reason for this is believed to be that the amount of malonic acid added to battery A2 is greater than that of battery A1, so the film derived from dicarboxylic acid formed on the surface of the positive electrode active material becomes thicker, which hinders the release of lithium ions. On the other hand, due to the formation of a thick film, the initial efficiency of battery A2 is higher than that of battery A1.
[0157] In the battery A2, a part of the decrease in the initial charge capacity is compensated by the improvement in the initial efficiency. Therefore, the capacity after the first charge and discharge can be maintained at a high capacity similar to the battery A1.
[0158] On the other hand, when comparing batteries C1 and C2 in which transition metal oxides with high Li content were not added to the positive electrode slurry, the initial charge capacity of battery C2 was lower than that of battery C1 due to the addition of dicarboxylic acid. Therefore, the improvement in initial charge capacity brought about by adding dicarboxylic acid / anhydride to the positive electrode material is an effect found when transition metal oxides with high Li content are used as positive electrode active materials.
[0159] The results of X-ray diffraction measurement of the positive electrode active material obtained by disassembling the secondary batteries A1 and A2 after charge and discharge showed that the diffraction lines of the mixture of the transition metal oxide with a high Li content and the third composite oxide were obtained. The half-peak width of the diffraction line of the (101) plane of the transition metal oxide with a high Li content was 12.6 times that of the strongest diffraction line of the third composite oxide for A1 and 10.9 times that of A2.
[0160] The present invention has been described with respect to the preferred embodiments at this stage, but these disclosures are not to be construed as limiting. Various modifications and changes should be apparent to those skilled in the art of the present invention upon reading the above disclosures. Therefore, it should be construed that the scope of the appended claims includes all modifications and changes without departing from the true spirit and scope of the present invention.
[0161] Industrial Applicability
[0162] The positive electrode of the present invention is useful as a positive electrode of a secondary battery used in a driving power source for personal computers, mobile phones, mobile devices, portable information terminals (PDAs), portable game consoles, cameras, etc., a main power source or auxiliary power source for driving a motor in a hybrid vehicle, plug-in HEV, etc., a driving power source for electric tools, vacuum cleaners, robots, etc.
[0163] Description of Reference Numerals
[0164] 1: secondary battery, 10: wound electrode group, 11: square battery case, 12: sealing plate, 13: negative electrode terminal, 14: positive electrode lead, 15: negative electrode lead, 16: gasket, 17: sealing plug, 17a: liquid injection hole, 18: frame.
Claims
1. A positive electrode material for a secondary battery, comprising: A high-Li-content transition metal oxide having an atomic ratio of lithium to oxygen: Li / O of 0.8 or more; and dicarboxylic acids and / or anhydrides of said dicarboxylic acids, The dicarboxylic acid comprises malonic acid.
2. The positive electrode material according to claim 1, in, The transition metal oxide with high lithium content is of the general formula (1): Li x1 M 1 A 1 2 represents a first composite oxide belonging to the space group Immm and satisfying 1.5≤x1≤2.3, M 1 contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe, A 1 Contains at least oxygen, Oxygen in A 1 The proportion of is 85 atomic % or more.
3. The positive electrode material according to claim 2, in, The first composite oxide has the general formula (1a): Li x1 M 1A 1- x2 M 1B x2 O 2-y A 2 y represents, and satisfies 0≤x2≤0.5 and 0≤y≤0.3, at least one of x2 and y is not 0, M 1A is at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe, M 1B It contains at least one selected from the group consisting of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta and W, A 2 At least one selected from the group consisting of F, Cl, Br, S and P is contained.
4. The positive electrode material according to claim 1, in, The transition metal oxide with high lithium content is of the general formula (2): Li x3 M 2 O z represents a second composite oxide belonging to the space group Pbca and satisfying 4≤x3≤7 and 3.5≤z≤5, M 2 Contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe.
5. The positive electrode material according to any one of claims 1 to 4, in, The positive electrode material further comprises a third composite oxide belonging to the space group R-3m, The third composite oxide has the general formula: Li x4 M 3 O 2 represents and satisfies 0.8≤x4≤1.2, M 3 The metal contains at least one selected from the group consisting of Ni, Co, Mn, Cu, Fe and Cr.
6. The positive electrode material according to claim 5, in, The ratio of the high-Li-content transition metal oxide to the total of the high-Li-content transition metal oxide and the third composite oxide is 0.3 to 20 mass %.
7. The positive electrode material according to any one of claims 1 to 4, in, The dicarboxylic acid and / or the anhydride of the dicarboxylic acid has 3 to 6 carbon atoms.
8. The positive electrode material according to claim 7, in, The anhydride of the dicarboxylic acid includes maleic anhydride.
9. A secondary battery comprising: a positive electrode, a negative electrode, and an electrolyte, The positive electrode has a positive electrode material layer, The positive electrode material layer includes the positive electrode material according to any one of claims 1 to 8.
10. The secondary battery according to claim 9, in, The positive electrode material layer contains the dicarboxylic acid and / or the anhydride of the dicarboxylic acid in a ratio of 0.1 to 10 mass %.
11. The secondary battery according to claim 9 or 10, in, The negative electrode comprises a negative electrode active material, The negative electrode active material comprises an alloy material. The alloy-based material includes at least one element selected from the group consisting of Si, Sn, Ga, and In.
12. The secondary battery according to claim 9 or 10, in, A portion of the positive electrode material has: LiM 4 O 2 An amorphous structure with LiFeO as the main component; 2 , CoO and MnO as the main component of any one of the group consisting of transition metal oxides; and / or selected from LiFeO 2 A transition metal oxide having as a main component a complex of at least two of the group consisting of CoO and MnO, M 4 Contains at least one selected from the group consisting of Ni, Co, Mn, Cu and Fe.
13. The secondary battery according to claim 9 or 10, in, In the charging state of 4.3V, metallic lithium is deposited on the negative electrode.
14. The secondary battery according to claim 9 or 10, in, At least a portion of the surface of the positive electrode material is covered with a coating film containing lithium, oxygen, and carbon.
